On the pure jump nature of crack growth for a class of pressure-sensitive elasto-plastic materials. (January 2022) - Dal Maso, Gianni; Toader, Rodica
Abstract: In the framework of a model for the quasistatic crack growth in pressure-sensitive elasto-plastic materials in the planar case, we study the properties of the length ℓ ( t ) of the crack as a function of time. We prove that, under suitable technical assumptions on the crack path, the monotone function ℓ is a pure jump function.